Human Muscle Progenitor Cells Displayed Immunosuppressive Effect through Galectin-1 and Semaphorin-3A - Séverine Lecourt; Yves Lepelletier; Valérie Vanneaux; Rafika Jarray; Thomas Domet; Françoise Raynaud; Réda Hadj-Slimane; Audrey Cras; Olivier Hermine; Jean-Pierre Marolleau; Jérôme Larghero (Stem Cells International)
In human skeletal muscle, myoblasts represent the main population of myogenic progenitors. We previously showed that, beside their myogenic differentiation capacities, myoblasts also differentiate towards osteogenic and chondrogenic lineages, some properties generally considered being hallmarks of mesenchymal stem cells (MSCs). MSCs are also characterized by their immunosuppressive potential, through cell-cell contacts and soluble factors, including prostaglandin E-2 (PGE-2), transforming growth factor-β1 (TGF-β1), interleukine-10, or indoleamine 2,3-dioxygenase. We and others also reported that Galectin-1 (Gal-1) and Semaphorin-3A (Sema-3A) were involved in MSCs-mediated immunosuppression. Here, we show that human myoblasts induce a significant and dose-dependant proliferation inhibition, independently of PGE-2 and TGF-β1. Our experiments revealed that myoblasts, in culture or in situ in human muscles, expressed and secreted Gal-1 and Sema-3A. Furthermore, myoblasts immunosuppressive functions were reverted by using blocking antibodies against Gal-1 or Sema-3A. Together, these results demonstrate an unsuspected immunosuppressive effect of myoblasts that may open new therapeutic perspectives.